One-year follow-up of young people with ME/CFS following infectious mononucleosis by Epstein-Barr virus - Pricoco, Rafael; Meidel, Paulina; Hofberger, Tim; Zietemann, Hannah; Mueller, Yvonne; Wiehler, Katharina; Michel, Kaja; Paulick, Johannes; Leone, Ariane; Haegele, Matthias; Mayer-Huber, Sandra; Gerrer, Katrin; et al. (Frontiers in Pediatrics, 2024)
Background Infectious mononucleosis after primary infection with Epstein-Barr virus (EBV-IM) has been linked to the development of myalgic encephalomyelitis/chronic fatigue-syndrome (ME/CFS) in children, adolescents, and young adults. Here, we present clinical phenotypes and follow-up data from a first German cohort of young people with ME/CFS following EBV-IM. Methods 12 adolescents and 13 young adults were diagnosed with IM-triggered ME/CFS at our specialized tertiary outpatient service by clinical criteria requiring post-exertional malaise (PEM) and a history of confirmed EBV primary infection as triggering event. Demographic information, laboratory findings, frequency and severity of symptoms, physical functioning, and health-related quality of life (HRQoL) were assessed and re-evaluated 6 and 12 months later. Results Young adults displayed more severe symptoms as well as worsening of fatigue, physical and mental functioning, and HRQoL throughout the study, compared to adolescents. After one year, 6/12 (54%) adolescents no longer met the diagnostic criteria for ME/CFS while all young adults continued to fulfill the Canadian consensus criteria. Improvement in adolescents was evident in physical functioning, symptom frequency and severity, and HRQoL, while young adults showed little improvement. EBV serology and EBV DNA load did not correlate with distinct clinical features of ME/CFS, and clinical chemistry showed no evidence of inflammation. Remarkably, the median time from symptom onset to ME/CFS diagnosis was 13.8 (IQR: 9.1–34.9) months. Conclusions ME/CFS following EBV-IM is a severely debilitating disease often diagnosed late and with limited responses to conventional medical care, especially in adults. Although adolescents may have a better prognosis, their condition can fluctuate and significantly impact their HRQoL. Our data emphasize that biomarkers and effective therapeutic options are also urgently needed to improve medical care and pave the way to recovery.